The chromatin remodelling complex NoRC safeguards genome stability by heterochromatin formation at telomeres and centromeres - Poste̜pska-Igielska, Anna; Krunic, Damir; Schmitt, Nina; Greulich-Bode, Karin Maria; Boukamp, Petra; Grummt, Ingrid (EMBO reports, 2013)
Constitutive heterochromatin is crucial for the integrity of chromosomes and genomic stability. Here, we show that the chromatin remodelling complex NoRC, known to silence a fraction of rRNA genes, also establishes a repressive heterochromatic structure at centromeres and telomeres, preserving the structural integrity of these repetitive loci. Knockdown of NoRC leads to relaxation of centromeric and telomeric heterochromatin, abnormalities in mitotic spindle assembly, impaired chromosome segregation and enhanced chromosomal instability. The results demonstrate that NoRC safeguards genomic stability by coordinating enzymatic activities that establish features of repressive chromatin at centromeric and telomeric regions, and this heterochromatic structure is required for sustaining genomic integrity.